Block trading, information asymmetry, and the informativeness of trading: Evidence from Chinese security markets. Issue 3 (17th August 2015) - Pan, Ningning; Zhu, Hongquan
Abstract : Purpose: – The purpose of this paper is to investigate how block trading and asymmetric information contribute to the firm-specific information measured by the stock return synchronicity. Based on China stock market which is dominated by individual investors, this study focus on whether traders of block trading, which are usually institutional investors, are "information trader." Design/methodology/approach: – Based on the high frequency data, the paper constructs two measures of information asymmetry, intraday measure and inter-day measure. Then the paper constructs a multiple regression model and examine how block trading and information asymmetry contribute to the firm-specific information measured by the stock return synchronicity. Findings: – The results show that: on the one hand, block trading transmits more firm-specific information, and can reduce the synchronicity; on the other hand, when the degree of information asymmetry is higher, block trading contains more firm-specific information and has a stronger effect on synchronicity. The effect of information asymmetry specifically displays as: block trading during the first half-hour of the trading day has a stronger effect on synchronicity; and block trading occurred in the days with publicly announced trading information has greater impact on synchronicity. Practical implications: – The conclusions have important practical implications: for market regulators, monitoring for block trading can improve the recognition and prevention of insider trading; for individual investors, especially the risk aversion investors, recognition of intraday and inter-day information asymmetry is beneficial for them to avoid the risk of asymmetric information. Originality/value: – First, the domestic and foreign research mostly concentrated impact of block trading on stock prices. However, reasons of stock price changes include the information effect and non-information effect, this paper selects stock return synchronicity as firm-specific information measure, and mainly focus on the information effect of block trading. Second, based on the high frequency data, the paper constructs two measures of information asymmetry, intraday measure and inter-day measure. Compared with general measure of information asymmetry, such as firm size, earnings quality, the two measures based on high frequency data are more precisely.